Micronutrients And Vitamin Analysis Of Bryonopsis Laciniosa Fruit - RAMYA.B; MALARVILI.T; VELAVAN.S (International Journal of Pharma and Bio Sciences, 2015)
The study was planned to analyse the vitamins and minerals present in Bryonopsis laciniosa fruit.Study revealed that the fruit contains Vitamins like C,D and E.Iron was found to be very much abundant and Calcium, Magnesium, Potassium, Chloride are in high amount. Sulphate and sodium are in a moderate level. Carbon, phosphorous, sodium, sulphur, zinc and manganese are substantially present while copper, Boron, selenium and molybdenum are present in trace amounts. These substances may be responsible for the health related properties which are based on their antioxidant, anticancer, antipyrectic, antiaphoretic, antidiabetic, anti-inflammation, antiheamatisum, antimicrobial and antiviral activity.